THE IMPACT OF SOCIAL CULTURE INFLUENCE AND CONSUMER ADVANTAGE ON THE ADOPTION OF E- COMMERCE - Shukri, Shakeerah Mohd; Johar; MGM; Tham, Jacquline (International Journal of Psychosocial Rehabilitation, 2020)
The aim related to this study is to explore the influence of social culture influence and consumer advantage on the adoption of E-commerce in Malaysia. Data were gather from the private companies of Malaysia and SPSS was used for the analysis of the data. The results revealed that the growths of electronic application have promoted the growth of business indirectly. Advances in electronic banking technology through daily banking affairs had created open doors for business to handling electronic document especially via the online banking channel. Throughout the world, online banking has been leading the e-commerce world into greater heights of business and consumer market. Consumer acceptance of online banking services had been the main catalyst for the growth of E- commerce. This is also true in Malaysia, rapid individual blog that turn into business had been flourishing. World is experiencing the industrial revolution, it changes the industries functionalities and all the way to how the product affect the market place. This attributes to the increasing use of internet in business. It has changed how company sell product to customer and distributed them to retailers.